Математична модель трифазного асинхронного мотора в однофазному стані - Чабан, В.Й.; Гоголь, З.І. (Електротехніка і електромеханіка, 2011)
In the paper, a mathematical model of a three-phase induction motor without a capacitor bank in a single-phase state is introduced. Differential equations of the electromechanical state are given in normal Cauchy’s form. Current jumping under commutation is taken into consideration. Results of transient process computation are given.